2021
DOI: 10.1039/d0cp06464e
|View full text |Cite
|
Sign up to set email alerts
|

Stability of pyruvic acid clusters upon slow electron attachment

Abstract: Pyruvic acid represents a key molecule in prebiotic chemistry and it has recently been proposed to be synthesized on interstellar ices. In order to probe the stability of pyruvic acid...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Pyruvic acid (PA), [CH 3 COCOOH], the simplest form of α-keto acids, has gained considerable interest as a model system in the last few decades because of its variable physical and structural properties in various phases. , Previous studies reported the monomeric structure and aggregated structures of PA in liquid, condensed, and gas phases. , In an IR/Raman spectroscopy study in 1981, a cyclic intermolecular hydrogen-bonded dimer structure with two CO groups in a trans configuration was observed in the liquid state . Note that shortly before in 1977, a nearly similar structure was characterized in the crystal form at ∼263 K by X-ray diffraction where COs are tilted by 3.5° compared to the trans configuration as reported in the liquid state .…”
Section: Introductionmentioning
confidence: 99%
“…Pyruvic acid (PA), [CH 3 COCOOH], the simplest form of α-keto acids, has gained considerable interest as a model system in the last few decades because of its variable physical and structural properties in various phases. , Previous studies reported the monomeric structure and aggregated structures of PA in liquid, condensed, and gas phases. , In an IR/Raman spectroscopy study in 1981, a cyclic intermolecular hydrogen-bonded dimer structure with two CO groups in a trans configuration was observed in the liquid state . Note that shortly before in 1977, a nearly similar structure was characterized in the crystal form at ∼263 K by X-ray diffraction where COs are tilted by 3.5° compared to the trans configuration as reported in the liquid state .…”
Section: Introductionmentioning
confidence: 99%
“…20 The same research group later investigated the fragmentation pathways of electron attachment to pyruvic acid clusters. 21 Despite the extensive studies, the adiabatic electron affinity (EA) of this important molecule has not been reported. Here, we have measured the kinetics for gas-phase electron attachment to PA and detachment from PA − in a flowing afterglow from 300 to 515 K and derive the EA from that data.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was recently reported that PA can accept an excess electron to form the thermodynamically stable PA – anion: Zawadzki et al observed PA – from low-energy electron attachment to gas-phase PA, as well as a number of anion fragments . The same research group later investigated the fragmentation pathways of electron attachment to pyruvic acid clusters . Despite the extensive studies, the adiabatic electron affinity (EA) of this important molecule has not been reported.…”
Section: Introductionmentioning
confidence: 99%